SERUM LIPID PROFILE AS A PROGNOSTIC INDICATOR FOR SEVERITY IN SEPSIS - Dr. Sanketh J.; Dr. Vinay R.B; Dr. Chandan N; Dr. Arundhati R. Chitnis; Dr. Mohit A. Kalyankar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background In intensive care units (ICUs), sepsis is the primary cause of death for patients who are critically unwell. Sepsis may cause changes in lipid metabolism. The aim of present study was to evaluate the serum lipid profile as a prognostic indicator for severity in sepsis. Methods The cross sectional study was conducted in the tertiary care hospital in Channapatna(SRI CHAMUNDESHWARI MEDICAL COLLEGE HOSPITAL AND RESEARCH INSTITUTE), India from the Department of General Medicine over a period of 5 months from November 2023 to March 2024 among 75 patients admitted to the ICU and medical ICU with sepsis and who survived for more than 48 hours. All the basic and lipid profile investigations were done and results were analyzed using SPSS version 25.0. Results Out of 75 patients with severe sepsis 8% of patients died during the hospital stay and 92% patients survived and were discharged from the hospital. The mean age of patients in survived and non survived groups was between 60 and 70 years. The mean APACHE II score among survived patients was 27.12± 3.8 and in non survived was 24.31±2.8. The length of hospital stay was 5.8 days among survived and 5.5 days among non survived. The level of TG was significantly higher in non-survivors than in survivors. Cholesterol, HDL, and LDL levels did not show statistically significant differences between the two groups Conclusion Our study found that In patients with severe sepsis, lipoprotein concentrations fluctuate quickly. The HDL fractions show the pattern of an early, sharp drop in cholesterol and a delayed recovery in the LDL fractions. Hence some lipoproteins may be used as a clinical indicator to assess the outcome of patients with sepsis.